2018
DOI: 10.3389/fsurg.2018.00027
|View full text |Cite
|
Sign up to set email alerts
|

Is There Any Role for D3 Lymphadenectomy in Gastric Cancer?

Abstract: Although D2 constitutes the level of lymph node dissection which most surgical associations endorse in their treatment guidelines for gastric cancer more extended D3 dissection has also been attempted to improve oncologic outcomes. Existing literature pertinent with the provisional therapeutic impact of D3 lymphadenectomy in advanced gastric cancer is studied in this mini review. Seven non-randomized comparisons, three randomized trials and five meta-analyses, almost exclusively of Asian origin, were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…As a matter of fact, it requires dissection around large important vessels that are located in deep retroperitoneal space causing a major surgical stress and injury. Available data suggest that D3 can be safely performed only if done in high expert volume specialized centers and by adequately trained surgeons [13].…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, it requires dissection around large important vessels that are located in deep retroperitoneal space causing a major surgical stress and injury. Available data suggest that D3 can be safely performed only if done in high expert volume specialized centers and by adequately trained surgeons [13].…”
Section: Discussionmentioning
confidence: 99%
“…Controversy lies in whether to perform D2 or D2 + PALD surgery on patients with advanced GC [44] . According to relevant studies, once gastric tumors invade the subserosal (T3 phase), serosal (T4a phase) or adjacent structures (T4b phase), the metastatic risk of para-aortic lymph nodes (PANs) increases to 10-30% [45][46][47] .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent paper Rovielo et al [14] concluded D3 lymphadenectomy could be further explored in specialized centers for curative surgery of advanced GC, providing that an acceptable morbidity and no increase in mortality can be offered.…”
Section: Discussionmentioning
confidence: 99%